Nurse leaders' perceptions of leadership development needs for strengthening the nursing workforce: a South African pilot study - Mirriam Matandela; Goitsemang Lucy Chisale; Vhothusa Edward Matahela (Frontiers in Health Services)
BackgroundNurses are central to South Africa's healthcare system, yet the sector faces ongoing challenges, including workforce shortages, high workloads, limited career progression, and weak institutional support. These issues are exacerbated by the absence of a structured leadership development framework. In response, the national Department of Health, through the South African Nursing Leadership Initiative, launched a pilot study to explore nurse leaders' perceptions of leadership development needs prior to the development of a national Nursing Leadership Competency Framework. This study explored nurse leaders’ perceptions of the leadership capacity required to strengthen the nursing workforce and support national health priorities.MethodsA qualitative, exploratory study was conducted between May and July 2024, involving 153 purposively selected nurse leaders from four provinces. Data were collected through structured group narrative sessions, using semi-structured questionnaires aligned with global frameworks. A deductive thematic narrative analysis guided by Braun and Clarke's six-phase framework (2006) was employed to identify themes.ResultsThree central themes emerged consistently across the pilot provinces. (1) Workforce planning and career pathway development revealed persistent nursing shortages and limited opportunities for career advancement. (2) Capacity building through continuing professional development highlighted the need for structured in-service education and leadership training to address skills gaps. (3) Organisational support and leadership for retention underscored high workloads, inadequate institutional support and the absence of psychological safety, all contributing to poor retention and morale.ConclusionThis pilot study provides contextual insights into the leadership development needs of a limited group of nurse leaders, which will inform the refinement of data collection tools and the design of a larger, national study. The findings are not generalisable but offer valuable direction for developing a contextually grounded Nursing Leadership Competency Framework and supporting strategic leadership capacity-building aligned with South Africa's health system strengthening goals.